Analisis Pengaruh Career Growth, Compensation, Dan Job Satisfaction Sebagai Variabel Intervening Terhadap Turnover Intention Karyawan Di Pt. Imora Motor (Honda Jakarta Center) - Wandhan Galuh Chalyana dan Mukti Rahardjo (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
Turnover intention is essentially a desire to move employees from one workplace to another. This is a company's challenge in maintaining labor competition. Human resources are believed to be the main factor determining the success of an organization. This study aims to determine the effect of Career Growth on Turnover Intention Employees, Compensation effect on Turnover Intention, And influence Job Satisfaction as variable intervening to TurnOver Employees in PT. Imora Motor (Honda Jakarta Center). This research is expected to be able to help find out the main factors causing employee turnover intention and overcome the problem of Turnover Intention so that it helps companies reduce losses both in terms of costs and time. This research uses quantitative research methodology simple random sampling. The method used in sampling is purposive sampling. Purposive sampling is a sampling method by formulating certain criteria using primary data sources. The number of samples in this research were 164 respondents. The variables used in this study used Dependent Variables, Intervening Variables and Independent Variables, then to get conclusions in the research that carried out statistical tests with the aim of finding out which dependent variables would influence the independent variables in the study. This study used SPSS version 23 to carry out statistical tests, Results of testing that has been done, partial regression test (t) shows that each is dependent the variables studied (career growth, compensation, and job satisfaction) have a significant influence on independence variable (Turnover Intention).